Grassroots perspectives of Javanese Muslims on local kyai figures versus Islamic preachers in religious television broadcasts - Hidayat, Arief; Lasiyo, Lasiyo; Wahyono, Sugeng Bayu (Masyarakat, Kebudayaan dan Politik, 2025)
This study examines the views of grassroots Javanese Muslims in Wukirsari, Imogiri, and Yogyakarta toward the authority of local kyai and television preachers (ustadz/ustadzah on the screen). This study aims to analyze how advances in media technology change the pattern of Islamic knowledge transmission and challenge traditional religious authority. Using a critical phenomenological approach, this study examines how media exposure shapes public perception, elevating celebrity preachers through the appeal of popularity while marginalizing traditional kyai rooted in local pesantren and social relations. The findings show that television creates a form of hyperreality that simulates religious legitimacy through visual performance, so the boundaries between ulama based on scientific sanad and media-constructed religious figures become blurred. However, many local kyai demonstrate adaptability to the digital shift without losing their traditional authority or social closeness to the community. The novelty of this study lies in the understanding that the contestation between traditional and modern Islamic authority is not simply a change in the pattern of preaching but also a complex identity struggle in the digital landscape. This study shows that symbolic authority in Islam is increasingly mediated, negotiated, and contested at the grassroots level, influenced by cultural and technological heritage.